The Influence of Customer Engagement Through Social Media on the Trust of Islamic Boarding Schools (Study at the Hamalatul Quran Islamic Boarding School Putri Ringinagung Kediri, East Java) - Fatoni, Imam; Puji, Didik (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Trust in brands of Islamic Boarding School can be grown from the reciprocal relationship in an engagement. Customer engagement through social media is an attempt by a company to keep in touch with its customers through social media facilities. According to a survey, Facebook and Instagram is a social media with the highest involvement value. Facebook and Instagram are one of the most popular in Indonesia. Compared to others, from February to May 2022 the number of PPHQ Putri followers on Facebook and Instagram is very high, and PPHQ Putri engagement also has the highest level of engagement. Therefore, this study aims to see whether customer engagement by PPHQ Putri through Instagram social media has been able to create trust in the PPHQ Putri brand. There are 4 variables used in this study to establish customer engagement. Data collection was done online by distributing questionnaires to followers of PPHQ Putri Facebook and Instagram accounts who have interacted by giving likes and comments and reposting PPHQ Putri facebook and Instagram accounts at least 3 times to 100 respondents. This study aims to find a relationship from the existence of customer engagement to brand trust partially and simultaneously using multiple linear regression analysis. Based on the results of the analysis that has been done partially, of the four variables, 3 of them have a significant influence on the trust of the PPHQ Putri brand while the results of the analysis are simultaneously known that all variables together influence the brand trust.